Peroxisome proliferator‐activated receptor gamma ligands affect NF‐kB and cytokine synthesis in the porcine endometrium—An in vitro study - Kunicka, Zuzanna; Kurzynska, Aleksandra; Szydlowska, Anna; Mierzejewski, Karol; Bogacka, Iwona (American journal of reproductive immunology (1989), 2019)
Problem Cytokines, mediators of the immune response, are involved in the regulation of female reproductive processes during the estrous cycle and pregnancy. The present study aimed to investigate the effect of selected peroxisome proliferator‐activated receptor gamma (PPARγ) ligands on the expression of nuclear factor kappa B (NF‐κB) and selected cytokines, such as interleukin (IL)‐1β, ‐4, ‐6, ‐8, ‐10, and the leukemia inhibitory factor, in the porcine endometrium on days 10‐12 and 14‐16 of the estrous cycle (mid‐ and late luteal phase, respectively) or pregnancy (maternal recognition of pregnancy and beginning of implantation, respectively). Method of study Endometrial slices were incubated in vitro in the presence of PPARγ agonists, 15‐deoxy‐Δ12, 14‐prostaglandin J2 or rosiglitazone, and PPARγ antagonist T0070907. mRNA and protein levels in tissues were determined by real‐time PCR and Western blot. Results On days 10‐12 of the estrous cycle and days 14‐16 of pregnancy, PPARγ ligands enhanced the expression of NF‐κB, mRNA cytokines, and/or proteins. During the late luteal phase of the estrous cycle (days 14‐16) and maternal recognition of pregnancy (days 10‐12), PPARγ ligands inhibited the expression of NF‐κB, and they differentially affected the expression of mRNA and proteins of cytokines. Conclusion Our results indicate that PPARγ is engaged in the endometrial synthesis of NF‐κB and selected cytokines in pigs. The influence of PPARγ ligands on the tested components of the immune system varied subject to the physiological status of females, and it could be associated with differences in endometrial receptivity.